The Involvement of Metallothioneins in Mitochondrial Function and Disease - Lindeque, J.Z.; Levanets, O.; Louw, R.; van der Westhuizen, F.H. (Current Protein and Peptide Science, 2010)
Mitochondrial oxidative phosphorylation deficiency is accompanied by various down-stream, adaptive responses which play a key role in the varied phenotypes observed when mitochondrial dysfunction occurs. These responses are often accompanied by the induction of genes involved in defense mechanisms against oxidative stress. Among these responses, metallothioneins (MTs) has been identified to be responsive to mitochondrial dysfunction. MTs, which are expressed in four different isoforms, are small, cysteine rich, metal binding proteins that have been associated with a protective effect in cells under numerous diseased and stressed states. Their diverse functionality and protective roles can be ascribed to their three basic abilities or primary functions which are metal homeostasis, heavy metal detoxification and free radical scavenging. The involvement of MTs with numerous cellular processes, organelles and cells has received much attention while notice of their involvement with the function of mitochondria has been lacking. It is believed that MTs promote the survival of mitochondrial dysfunctional cells by acting as highly efficient reducing elements against the damaging properties of reactive oxygen species (ROS) and by limiting apoptosis. In addition to their role in mitochondrial disease, convincing evidence exist, albeit with conflicting results, of its involvement in some key functions of the mitochondrion, including redox modulation, metal homeostasis and enzyme and transcription factor regulation.
Keywords: oxidative stress